Avalanching glacier instabilities: Review on processes and early warning perspectives. (15th May 2015) - Faillettaz, Jérome; Funk, Martin; Vincent, Christian
Abstract Avalanching glacier instabilities are gravity‐driven rupture phenomena that might cause major disasters, especially when they are at the origin of a chain of processes. Reliably forecasting such events combined with a timely evacuation of endangered inhabited areas often constitute the most efficient action. Recently, considerable efforts in monitoring, analyzing, and modeling such phenomena have led to significant advances in destabilization process understanding, improving early warning perspectives. The purpose of this paper is to review the recent progress in this domain. Three different types of instabilities can be identified depending on the thermal properties of the ice/bed interface. If cold (1), the maturation of the rupture is associated with a typical time evolution of surface velocities and passive seismic activity. A prediction of the final break off is possible using these precursory signs. For the two other types, water plays a key role in the development of the instability. If the ice/bed interface is partly temperate (2), the presence of meltwater may reduce the basal resistance, which promotes the instability. No clear and easily detectable precursory signs are known in this case, and the only way to infer any potential instability is to monitor the temporal evolution of the thermal regime. The last type of instability (3) concerns steep temperate glacier tongues switching for several days/weeks during the melting season into a so‐called "active phase" followed in rare cases by a major break‐off event. Although the prediction of such events is still far from being achievable, critical conditions promoting the final instability can be identified.